Positive electrode material, preparation method and sodium ion battery

By doping transition metal elements and other components into the positive electrode material of the sodium ion battery, adjusting the interlayer structure, the migration problem of sodium ion battery at low charging rate is solved, and the rate performance and cycling performance are improved.

CN119208585APending Publication Date: 2024-12-27SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411301969.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing sodium ion battery positive electrode material narrows the sodium ion migration channel at low charging rate, resulting in a decrease in the ion migration rate, limiting the application of the material in power batteries.

Method used

By doping transition metal elements, lanthanides or gallium into layered oxides, the interlayer structure is adjusted, the migration path of sodium ions is broadened, the mobility of sodium ions is improved, and the SOC is reduced by 0-50% Sodium ion migration impedance under the

Benefits of technology

It effectively improves the rate performance of the positive electrode material, improves the cycle performance and stability of the battery, enhances the sodium ion mobility, and reduces the impedance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208585A_ABST
    Figure CN119208585A_ABST
Patent Text Reader

Abstract

The invention provides a positive electrode material, a preparation method and a sodium ion battery. The positive electrode material comprises a layered oxide, and the chemical formula of the layered oxide is Na < x > Ni Mn Fe < c > M < d > O < 2-delta >, wherein 0.67 < x < = 0.96, 0 < = a < = 1, 0 < = b < = 1, 0 < = c < = 1, 0 < = d < = 1, a + b + c + d = 1,-0.1 < = delta < = 0.5, and M is selected from at least one of transition metal elements, lanthanide elements and gallium. By doping elements with relatively high metal oxygen bond energy, such as transition metal elements, lanthanide elements or gallium, in the layered oxide, the interlayer structure of the layered oxide can be effectively adjusted, so that the migration path of sodium ions is widened, the migration rate of the sodium ions is improved, the migration impedance of the sodium ions under 0-50% SOC is reduced, the rate capability of the positive electrode material is improved, and the service life of the positive electrode material is prolonged. The cycle performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery material technology, and specifically relates to a positive electrode material and a preparation method, and a sodium ion battery. Background Art

[0002] Sodium-ion batteries (SIBs) have attracted worldwide attention due to the natural abundance and low cost of sodium. Leveraging the extensive experience gained with lithium-ion batteries, SIBs have rapidly developed. The primary cathode materials for SIBs include layered and tunnel-type transition metal oxides, polyanionic compounds, Prussian blue analogs, and organic materials. Layered oxides, with their periodic structure, simple preparation methods, and high specific capacity and voltage, are the primary cathode materials for SIBs.

[0003] Layered oxide materials, as cathode materials for sodium-ion batteries, offer the advantages of high capacity and high rate capability. However, complex phase transitions during the charge and discharge process can narrow the sodium ion migration channel at low charge rates (SOCs), significantly reducing the ion migration rate and increasing the ion migration impedance at low SOCs. This reduces both the battery rate capability and discharge power, limiting the material's application in power batteries.

[0004] Therefore, how to improve the rate performance of sodium ion positive electrode materials is a problem that needs to be solved at present. Summary of the Invention

[0005] The present application provides a positive electrode material and a preparation method, and a sodium ion battery, aiming to improve the ion mobility of the positive electrode material of the existing sodium ion battery at low SOC.

[0006] The first embodiment of the present application provides a positive electrode material, including a layered oxide, wherein the chemical formula of the layered oxide is Na x Ni a Mn b Fe c M d O 2-δ ; Wherein, 0.67<x≤0.96, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, a+b+c+d=1, -0.1≤δ≤0.5, M is selected from at least one of transition metal elements, lanthanide elements and gallium.

[0007] In some embodiments, the layered oxide has a sodium interlayer spacing d O-Na-O and the transition metal interlayer spacing d O-TM-O , satisfying: 1.5≤d O-Na-O / d O-TM-O ≤1.62.

[0008] In some embodiments, the sodium interlayer spacing d O-Na-O satisfy:

[0009] In some embodiments, the layered oxide has a transition metal interlayer spacing d O-TM-O satisfy:

[0010] In some embodiments, M is selected from at least one element of Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti, and Yb.

[0011] A second embodiment of the present application provides a method for preparing a positive electrode material, which is used to prepare the positive electrode material in any of the above embodiments, comprising the following steps:

[0012] Providing a sodium source and a M source, placing them in a solvent to form a solution;

[0013] A nickel-iron-manganese matrix is ​​provided, the solution is atomized, mixed with the nickel-iron-manganese matrix, and a sintering reaction is performed to obtain the positive electrode material.

[0014] In some embodiments, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium citrate, sodium gluconate, sodium acetate, sodium ethoxide, and sodium phenoxide.

[0015] In some embodiments, the M source includes at least one of a carbonate, a phosphate, a nitrate, a hydroxide, and an oxide of at least one element selected from the group consisting of Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti, and Yb;

[0016] The solvent includes at least one of water, ethanol and ethylene glycol.

[0017] In some embodiments, the molar ratio of the sodium source to the M source is 0.67-0.96:1.

[0018] In some embodiments, the step of atomizing the solution further comprises:

[0019] The solution is controlled to form droplets through the atomizing device, the flow rate of the solution through the atomizing device is 10-300 ml / min, and the gas pressure in the atomizing device is 0.3-0.7 MPa.

[0020] In some embodiments, the sintering reaction temperature is 500-1100°C.

[0021] In some embodiments, the sintering reaction time is 1 to 24 hours.

[0022] In some embodiments, the step of performing a sintering reaction further comprises:

[0023] A mixture of air and oxygen is circulated.

[0024] A third embodiment of the present application provides a sodium ion battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material of any of the above embodiments.

[0025] The present application provides a positive electrode material, including a layered oxide, the chemical formula of which is Na x Ni a Mn b Fe c M d O 2-δ Wherein, 0.67 < x ≤ 0.96, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1, 0 ≤ c ≤ 1, 0 ≤ d ≤ 1, a + b + c + d = 1, -0.1 ≤ δ ≤ 0.5, and M is selected from at least one of a transition metal element, a lanthanide element, and gallium. By doping the layered oxide with an element having a higher metallicity than sodium ions, such as a transition metal element, a lanthanide element, or gallium, the interlayer structure of the layered oxide can be effectively adjusted, thereby broadening the sodium ion migration path, increasing sodium ion mobility, and reducing sodium ion migration resistance at a SOC of 0 to 50%, thereby improving the rate capability of the positive electrode material and the cycling performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] The following detailed description of the specific embodiments of the present application in conjunction with the accompanying drawings will make the technical solutions and other beneficial effects of the present application apparent.

[0027] Figure 1 This is an XRD test result diagram of a positive electrode material provided in the examples and comparative examples of the present application;

[0028] Figure 2 This is a graph showing the ion mobility test results of a sodium ion battery provided in the examples and comparative examples of the present application. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the embodiments described are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative efforts are within the scope of protection of this application.

[0030] In the description of this application, it should be noted that, unless otherwise clearly specified and limited, the terms "connected" and "connected" should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be directly connected, or indirectly connected through an intermediate medium, or indirectly connected through a pipe or pipeline, and it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in this application can be understood according to the specific circumstances. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly specified and specifically limited. In addition, the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more features.

[0031] The first embodiment of the present application provides a positive electrode material, including a layered oxide, the chemical formula of which is Na x Ni a Mn b Fe c M d O 2-δ ; Wherein, 0.67<x≤0.96, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤d≤1, a+b+c+d=1, -0.1≤δ≤0.5, M is selected from at least one of transition metal elements, lanthanide elements and gallium.

[0032] For O3 phase materials, the main phase change during the battery charge and discharge process is O3→P3→O3. During the discharge process, the layered oxide in the positive electrode material changes from P phase to O phase, and NaO6 changes from a triangular prism structure to an octahedral structure. The sodium interlayer spacing (d O-Na-O ) changes from large to small, which will cause the sodium ion migration channel at low SOC (0-50%) to narrow and the ion migration rate to drop significantly. The layered oxides provided by the present application are doped with transition metal elements, lanthanides or gallium, which are more metallic elements. They can effectively enhance the bond energy of the metal-oxygen bond in the transition metal layer, reduce the distance between the transition metal layers, and expand the distance between the sodium layers, thereby widening the sodium ion migration path, increasing the sodium ion mobility, and reducing the sodium ion migration impedance at 0-50% SOC, thereby improving the rate performance of the positive electrode material and improving the cycle performance of the battery.

[0033] In some embodiments, the layered oxide has an interlayer spacing d O-Na-O and the transition metal interlayer spacing d O-TM-O , satisfying: 1.5≤d O-Na-O / d O-TM-O ≤1.62.

[0034] Understandably, d O-Na-O / d O-TM-O The value of can be any value among 1.5, 1.52, 1.54, 1.56, 1.58, 1.6, 1.62 or the range between any two values. The coordination between the sodium interlayer spacing and the transition metal interlayer spacing affects the electrical properties of the positive electrode material. Properly increasing the sodium interlayer spacing and reducing the transition metal interlayer spacing can broaden the migration path of sodium ions and improve the sodium ion mobility. When the sodium interlayer spacing is too large, a phase transition may occur, resulting in a decrease in sodium storage capacity. When the sodium interlayer spacing and the transition metal interlayer spacing meet the above relationship, the sodium ion migration path can be broadened, the sodium ion mobility can be improved, the migration of metal ions in the transition metal layer, the Jan-Taylor effect, etc. can be reduced while ensuring sufficient sodium storage capacity, thereby improving the material stability.

[0035] It should be noted that the transition metal layer can not only be an atomic layer containing transition metal elements, but also an atomic layer containing elements with metallic properties similar to those of transition metal elements. Elements with metallic properties similar to those of transition metal elements can be metal elements such as lanthanides and gallium.

[0036] In some embodiments, the sodium interlayer spacing d O-Na-O satisfy:

[0037] It can be understood that the sodium interlayer distance d O-Na-O The value of (unit: ) can be any value among 3.4, 3.45, 3.5, 3.55 or the range between any two values. O-Na-O Meeting the above value range can enable sodium ions to have a wider migration path in the layered oxide, thereby improving the battery rate.

[0038] In some embodiments, the layered oxide has a transition metal interlayer spacing d O-TM-O satisfy:

[0039] It is understood that the transition metal interlayer distance d O-TM-O The value of (unit: ) can be any value among 2.19, 2.21, 2.23, 2.25, 2.27, 2.29 or the range between any two values. O-TM-O Meeting the above value range can ensure that sodium ions have an ideal mobility while the layered oxide as a whole has good structural stability, reduce the stress and strain of the positive electrode material, and improve the cycle life of the positive electrode material.

[0040] In some embodiments, the molar ratio of sodium element to elements (Ni+Mn+Fe+M) in the layered oxide is 0.67-0.96:1.

[0041] It is understood that the molar ratio of sodium to metal elements (Ni+Mn+Fe+M) in the layered oxide can be any value among 0.67, 0.73, 0.80, 0.87, 0.93, 0.96, or a range between any two values. When the molar ratio of sodium to metal elements (Ni+Mn+Fe+M) satisfies the above range, the layered oxide can have an ideal interlayer structure and thus have good ion mobility.

[0042] In some embodiments, M is selected from at least one element of Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti, and Yb.

[0043] A second embodiment of the present application provides a method for preparing a positive electrode material, which is used to prepare the positive electrode material in any of the above embodiments, comprising the following steps:

[0044] Providing a sodium source and a M source, placing them in a solvent to form a solution;

[0045] A nickel-iron-manganese matrix is ​​provided, the solution is atomized, mixed with the nickel-iron-manganese matrix, and a sintering reaction is performed to obtain a positive electrode material.

[0046] The nickel-manganese-iron matrix can be prepared by conventional existing preparation methods.

[0047] Compared to the solid-phase sintering method for preparing positive electrode materials, the sodium source and the M source are formed into a solution and then atomized, and then mixed with the nickel-iron-manganese matrix for a single sintering. The layered oxide obtained by the preparation method provided in this embodiment has good doping uniformity, and there is no need to add excessive raw materials. Most of the doping elements can enter the lattice well, and then form covalent bonds with oxygen atoms, which stabilizes the structure and changes the interlayer spacing. At the same time, the form of the solution can avoid the problem of poor crystallinity of the positive electrode material caused by uneven sodiumization in the solid-phase sintering process. There is no need to add excessive raw materials so that the residual alkali content on the surface of the final positive electrode material is small, and the sodium interlayer spacing and the transition metal interlayer spacing can be accurately regulated, which is beneficial to the processing and gas production of the later-stage manufacturing battery.

[0048] In some embodiments, the sodium source and the M source can be dissolved in separate solvents to form a sodium source solution and an M source solution, respectively, which are then atomized and mixed with the nickel-manganese-iron matrix. By preparing separate sodium and M source solutions, they can be more evenly dispersed in the solution, facilitating the formation of a more uniformly doped layered oxide during the subsequent sintering reaction.

[0049] In some embodiments, the sodium source includes at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide and an organic sodium salt, wherein the organic sodium source can be selected from at least one of sodium citrate, sodium gluconate, sodium acetate, sodium ethoxide and sodium phenol.

[0050] In some embodiments, the M source includes at least one of a carbonate, a phosphate, a nitrate, a hydroxide, and an oxide of at least one of Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti, and Yb;

[0051] The solvent includes at least one of water, ethanol, and ethylene glycol.

[0052] In some embodiments, the added amount of the sodium source and the M source is 0.67-0.96:1 by mole.

[0053] In some embodiments, the step of atomizing the solution further comprises:

[0054] The solution is controlled to form droplets through the atomizing device, the flow rate of the solution through the atomizing device is 10-300 ml / min, and the gas pressure in the atomizing device is 0.3-0.7 MPa.

[0055] It is understandable that the value of the flow rate of the solution through the atomizing device (unit: ml / min) can be any value in 10, 50, 100, 150, 200, 250, 300 or the range between any two values; the value of the gas pressure in the atomizing device (unit: MPa) can be any value in 0.3, 0.4, 0.5, 0.6, 0.7 or the range between any two values. Among them, the atomizing device can be a device commonly used in the art such as an atomizer and a sprayer, which will not be repeated here. By controlling the flow rate of the solution through the atomizing device and the pressure in the atomizing device, it is possible to ensure that the solution forms sufficiently dispersed and uniform droplets after atomization, so that it can be fully mixed with the nickel-manganese-iron matrix in the reaction chamber, and accurately control the sodium interlayer spacing and the transition metal interlayer spacing, which is beneficial to the processing and gas production of the later manufacturing battery.

[0056] In some embodiments, the sintering reaction temperature is 500-1100°C.

[0057] In some embodiments, the sintering reaction time is 1 to 24 hours.

[0058] It is understood that the sintering reaction temperature (unit: ° C) can be any value of 500, 600, 700, 800, 900, 1000, 1100, or a range between any two values; the sintering reaction time (unit: h) can be any value of 1, 4, 8, 12, 16, 20, 24, or a range between any two values. When the sintering reaction temperature and time each meet the above ranges, the sodium source, M source, and nickel-manganese-iron matrix undergo melting and redox reaction to generate the final desired positive electrode material.

[0059] In some embodiments, the step of performing a sintering reaction further comprises:

[0060] A mixture of air and oxygen is circulated.

[0061] By circulating a mixture of air and oxygen as the sintering atmosphere, the oxidation reaction of the material can be promoted, and the oxygen partial pressure during the sintering process can be regulated, so that the final positive electrode material has a good pore structure.

[0062] Specifically, the preparation method provided in the above embodiment can be achieved by the following steps:

[0063] S1, dissolving the M source and the sodium source in a solvent to form a solution;

[0064] S2, atomizing the solution and mixing it with the nickel-iron-manganese matrix in the main reaction chamber, introducing circulating gas into the main reaction chamber, adjusting the circulating gas temperature in the main chamber, and performing a sintering reaction;

[0065] S3. The material obtained after the sintering reaction is crushed and sieved to obtain a positive electrode material.

[0066] A third embodiment of the present application provides a sodium ion battery, comprising a positive electrode sheet, wherein the positive electrode sheet comprises the positive electrode material of any of the above embodiments.

[0067] The following describes the positive electrode material, preparation method, and sodium ion battery provided in this application in conjunction with specific embodiments:

[0068] Example 1

[0069] Example 1 provides a positive electrode material, including a chemical formula of Na 0.945 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.95 Ga 0.05 The layered compound of O2 is prepared by the following steps:

[0070] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-gallium oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0071] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0072] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0073] The sodium salt ratio in the tested positive electrode material was 0.945.

[0074] The content of main elements in the positive electrode material was tested by ICP: 0.2 g of sample was weighed and digested in 5 ml of hydrochloric acid at 200 ° C until completely dissolved. After two dilutions (100 ml), the dilution solution was placed in the ICP equipment for testing. The quantitative method used the standard curve method to quantitatively test Na, Ni, Fe, Mn, and M.

[0075] XRD test was carried out to confirm the material structure. The specific test conditions of XRD were as follows: Cu target, K as X-ray source, tube voltage 40kV, tube current 100mA, test range 10°~90°, scanning speed 2° / min, and the results were as follows: Figure 1 shown.

[0076] The material is calculated d O-Na-O / d O-TM-O =1.60.

[0077] The positive electrode material prepared in the above steps is used to prepare a button battery. The specific steps are as follows:

[0078] The positive electrode sheet is composed of the aforementioned positive electrode materials, conductive carbon black, and a binder, polyvinylidene fluoride (PVDF), mixed in a mass ratio of 90:5:5. Using N-methylpyrrolidone (NMP) as a solvent, the slurry is evenly coated on aluminum foil, dried at an appropriate temperature, rolled to the desired thickness, and vacuum-dried at 120°C for 12 hours to obtain the positive electrode sheet. The negative electrode uses a sodium metal sheet, the separator is a polypropylene porous membrane, and the electrolyte is a 1 mol / L NaPF6 / EC+DEC+DMC (EC:DEC:DMC = 1:1:1 by volume).

[0079] Example 2

[0080] Example 2 provides a positive electrode material, including a chemical formula of Na 0.96 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.95 Ga 0.05The layered compound of O2 is prepared by the following steps:

[0081] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-gallium oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0082] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0083] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0084] The sodium salt ratio in the tested positive electrode material was 0.96.

[0085] XRD test was carried out to confirm the material structure. The specific test conditions of XRD were as follows: Cu target, K as X-ray source, tube voltage 40kV, tube current 100mA, test range 10°~90°, scanning speed 2° / min, and the results were as follows: Figure 1 shown.

[0086] The material is calculated d O-Na-O / d O-TM-O =1.56.

[0087] Example 3

[0088] Example 3 provides a positive electrode material, including a chemical formula of Na 0.675 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.95 Ga 0.05 The layered compound of O2 is prepared by the following steps:

[0089] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-gallium oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0090] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0091] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0092] The sodium salt ratio in the tested positive electrode material was 0.675.

[0093] The material is calculated d O-Na-O / d O-TM-O =1.61.

[0094] Example 4

[0095] Example 4 provides a positive electrode material, including a chemical formula of Na 0.93 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.99 Ga 0.01 The layered compound of O2 is prepared by the following steps:

[0096] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-gallium oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0097] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0098] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0099] The sodium salt ratio in the tested positive electrode material was 0.93.

[0100] The material is calculated d O-Na-O / d O-TM-O =1.54.

[0101] Example 5

[0102] Example 5 provides a positive electrode material, including a chemical formula of Na 0.96 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.99 Ga 0.02 The layered compound of O2 is prepared by the following steps:

[0103] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-gallium oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0104] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0105] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0106] The sodium salt ratio in the tested positive electrode material was 0.96.

[0107] The material is calculated d O-Na-O / d O-TM-O =1.5.

[0108] Comparative Example 1

[0109] Comparative Example 1 provides a positive electrode material comprising a chemical formula of Na 0.95 Ni 0.4 Fe 0.2 Mn 0.4 The layered compound of O2 is prepared by the following steps:

[0110] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol to form a sodium carbonate solution;

[0111] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0112] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0113] The sodium salt ratio in the tested positive electrode material was 0.943.

[0114] XRD test was carried out to confirm the material structure. The specific test conditions of XRD were as follows: Cu target, K as X-ray source, tube voltage 40kV, tube current 100mA, test range 10°~90°, scanning speed 2° / min, and the results were as follows: Figure 1 shown.

[0115] The material is calculated d O-Na-O / d O-TM-O =1.38.

[0116] The sodium ion battery was prepared using the above-mentioned positive electrode material, and the preparation method was consistent with that in Example 1.

[0117] Comparative Example 2

[0118] Comparative Example 2: A positive electrode material and a sodium ion battery were prepared using the same preparation method as in Example 1, with the only difference being the adjustment of reactants and process parameters, as shown in Table 1.

[0119] Example 1 provides a positive electrode material, including a chemical formula of Na 0.98 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.99 La 0.01 The layered compound of O2 is prepared by the following steps:

[0120] S1. Solution preparation: dissolve sodium carbonate in ethylene glycol and suspend nano-lanthanum oxide in ethanol to form sodium carbonate solution and nano-gallium oxide solution;

[0121] S2. The sodium carbonate solution and the nano-gallium oxide solution are atomized by an atomizing device and delivered to the main reaction chamber, where they are evenly mixed with the nickel-iron-manganese matrix in the main chamber. The circulating air is heated at a heating rate of 4°C / min, and finally heated to 800°C, with continuous circulation for 8 hours.

[0122] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0123] The sodium salt ratio in the tested positive electrode material was 0.98.

[0124] The material is calculated d O-Na-O / d O-TM-O =1.43.

[0125] Comparative Example 3

[0126] Comparative Example 2 provides a positive electrode material including a chemical formula of Na 0.926 (Ni 0.4 Fe 0.2 Mn 0.4 ) 0.95 Ga 0.05 The layered compound of O2 is prepared by the following steps:

[0127] S1. Solid phase mixing: Sodium carbonate, nickel iron manganese matrix and gallium oxide are mixed by stirring;

[0128] S2, calcining the mixed materials in air at a calcination temperature of 800°C and a holding time of 8h;

[0129] S3. After sintering, the material is crushed and sieved to obtain the positive electrode material.

[0130] The sodium salt ratio in the tested positive electrode material was 0.926.

[0131] XRD test was carried out to confirm the material structure. The specific test conditions of XRD were as follows: Cu target, K as X-ray source, tube voltage 40kV, tube current 100mA, test range 10°~90°, scanning speed 2° / min, and the results were as follows: Figure 1 shown.

[0132] The material is calculated d O-Na-O / d O-TM-O =1.44.

[0133] The sodium ion battery was prepared using the above-mentioned positive electrode material, and the preparation method was consistent with that in Example 1.

[0134] Table 1

[0135]

[0136] The surface residual alkali of the positive electrode materials in the above embodiment and comparative example was detected, and the batteries in the above embodiment and comparative example were subjected to GITT test. The test steps are as follows:

[0137] Each cycle is set to 5% discharge depth, let it stand for 30 minutes, discharge at a low rate for 30 minutes, let it stand for 15 minutes, cycle 20 times, and then reuse. The ion mobility of each cycle is calculated and the results are as follows: Figure 2 and as shown in Table 2.

[0138] Table 2

[0139]

[0140] according to Figure 2 It can be seen that the layered oxide of the positive electrode material provided in Example 1 has a reasonable sodium interlayer spacing and transition metal interlayer spacing compared to the layered oxide of the positive electrode material provided in Comparative Example 1. Therefore, the positive electrode material provided in Example 1 has better and more stable ion mobility than the positive electrode material provided in Comparative Example 1.

[0141] Table 2 shows that the positive electrode materials obtained using the solutions provided in this application all exhibit good capacity retention and low surface residual alkali. Comparative Examples 1 to 3 show that when the proportion of sodium in the positive electrode material exceeds the range protected by this application, excessive residual alkali forms on the material surface; at the same time, the interlayer spacing of the layered oxide is affected, resulting in low battery capacity retention.

[0142] The above is a detailed introduction to a positive electrode material and preparation method, and a sodium ion battery provided in the embodiments of the present application. Specific examples are used in this application to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the technical solutions and core ideas of the present application. Ordinary technicians in this field should understand that they can still modify the technical solutions recorded in the aforementioned embodiments, or replace some of the technical features therein with equivalents; and these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A positive electrode material, characterized in that: comprising a layered oxide, the chemical formula of the layered oxide being Na x Ni a Mn b Fe c M d O 2-δ ; wherein, 0.67 < x ≤ 0.96, 0 ≤ a ≤ 1, 0 ≤ b ≤ 1, 0 ≤ c ≤ 1, 0 ≤ d ≤ 1, a + b + c + d = 1, -0.1 ≤ δ ≤ 0.5, and M is selected from at least one of transition metal elements, lanthanide elements, and gallium.

2. A positive electrode material according to claim 1, characterized in that: The layered oxide has a sodium interlayer spacing d O-Na-O and the transition metal interlayer spacing d O-TM-O , satisfying: 1.5≤d O-Na-O / d O-TM-O ≤1.

62.

3. A positive electrode material according to claim 2, characterized in that: The sodium interlayer spacing d O-Na-O satisfy: and / or, The layered oxide has a transition metal interlayer spacing d O-TM-O satisfy:

4. A positive electrode material according to claim 1, characterized in that: The M is selected from at least one element of Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti, and Yb.

5. A method for preparing a positive electrode material according to any one of claims 1 to 4, characterized in that: The steps include: Providing a sodium source and a M source, placing them in a solvent to form a solution; A nickel-iron-manganese matrix is ​​provided, the solution is atomized, mixed with the nickel-iron-manganese matrix, and a sintering reaction is performed to obtain the positive electrode material.

6. The method for preparing a positive electrode material according to claim 5, characterized in that: The sodium source comprises at least one of sodium carbonate, sodium bicarbonate, sodium hydroxide, sodium citrate, sodium gluconate, sodium acetate, sodium ethoxide and sodium phenolate; and / or, The M source includes at least one of carbonate, phosphate, nitrate, hydroxide and oxide of at least one element among Zr, Ga, Ta, La, Ce, Nd, Y, Nb, W, Ti and Yb; The solvent includes at least one of water, ethanol and ethylene glycol.

7. The method for preparing a positive electrode material according to claim 5, characterized in that: The molar ratio of the sodium source to the M source is 0.67-0.96:

1.

8. The method for preparing a positive electrode material according to claim 5, characterized in that: The step of atomizing the solution further comprises: The solution is controlled to form droplets through the atomizing device, the flow rate of the solution through the atomizing device is 10-300 ml / min, and the gas pressure in the atomizing device is 0.3-0.7 MPa.

9. The method for preparing a positive electrode material according to claim 5, characterized in that: The sintering reaction temperature is 500-1100° C.; and / or, The sintering reaction time is 1 to 24 hours; and / or, The step of performing a sintering reaction further comprises: A mixture of air and oxygen is circulated.

10. A sodium ion battery, comprising a positive electrode sheet, characterized in that: The positive electrode sheet comprises the positive electrode material as described in any one of claims 1 to 4 or comprises the positive electrode material prepared by the preparation method as described in any one of claims 5 to 9.

Citation Information

Cited By

  • Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

    CN121282158A

  • Lanthanum-doped nickel-manganese-based sodium-ion battery positive electrode material as well as preparation method and application thereof

    CN121687942A